Introduction of VISIONSENSE® for indocyanine green fluorescence-guided parathyroidectomy: Report of a case. (2020) - Kamada, Teppei; Yoshida, Masashi; Suzuki, Norihiko; Takeuchi, Hideyuki; Takahashi, Junji; Marukuchi, Rui; Narihiro, Satoshi; Ohdaira, Hironori; Suzuki, Yutaka
Highlights: NIR overlay threshold function of VISIONSENSE® allows us to set a floor for the NIR signal to be included in the overlay. We report the case of a patient who underwent indocyanine green fluorescence-guided parathyroidectomy using the threshold-adjustment function of VISIONSENSE®. The threshold-adjustment function of VISIONSENSE® may be useful to readily identify the PG in parathyroid surgery. Abstract: Introduction: VISIONSENSE® is a new near-infrared (NIR) fluorescence laparoscope and has an NIR overlay threshold function that allows us to set a floor for the NIR signal to be included in the overlay. We report the case of a patient who underwent indocyanine green (ICG) fluorescence-guided parathyroidectomy for primary hyperparathyroidism due to parathyroid adenoma using the threshold-adjustment function of VISIONSENSE®. Presentation of case: A 40-year-old man was referred to our department for examination and treatment of hypercalcemia. ICG fluorescence-guided parathyroidectomy using VISIONSENSE® was planned on diagnosis of primary hyperparathyroidism due to parathyroid tumor. In the operation, we were unable to readily recognize the parathyroid gland (PG). After intravenous injection of ICG, fluorescence from ICG appeared from the left thyroid lobe to the PG, but PG contours remained unclear. We therefore used the threshold-adjustment function of VISIONSENSE® to discard NIR signal values <50%. Clear contours of the PG were subsequently obtained, allowing recognition of the gland and successful ICG-guided parathyroidectomy. No postoperative complications were encountered and the pathological diagnosis was parathyroid adenoma. Discussion: In our case, both PG and thyroid showed ICG fluorescence, but the intensity of thyroid fluorescence was slightly little lower than that of PG fluorescence. To differentiate between fluorescence from PG and thyroid, the threshold-adjustment function of VISIONSENSE® may prove useful. Conclusion: This case suggests that the threshold-adjustment function of VISIONSENSE® may be useful to readily identify the PG in parathyroid surgery.